Decentralization and School-Based Management: A Comparative Study of Public and Private Schools in Jambi, Indonesia - Yulia Wiji Astika; Teta Wismar (Enigma in Education, 2024)
Decentralization and school-based management (SBM) have been widely adopted in Indonesia to enhance the quality and efficiency of education. This study investigates the implementation of SBM in public and private schools in Jambi Province, Indonesia, and explores its effects on school autonomy, teacher participation in decision-making, and student achievement. A mixed-methods approach was employed. Quantitative data were collected from 300 teachers and 600 students in 15 public and 15 private schools in Jambi Province using questionnaires and achievement tests. Qualitative data were gathered through semi-structured interviews with 30 school principals and 30 school committee members. Private schools demonstrated significantly higher levels of school autonomy and teacher participation in decision-making compared to public schools. However, no significant difference was found in student achievement between the two types of schools. Qualitative data provided insights into the challenges and opportunities associated with SBM implementation in both public and private schools. In conclusion, this study highlights the importance of contextual factors in shaping the implementation and outcomes of SBM. While private schools appear to have embraced SBM more effectively in terms of autonomy and participation, the impact on student achievement requires further investigation. The findings have implications for policymakers and school leaders seeking to enhance the effectiveness of SBM in Indonesia.